2014
DOI: 10.1016/j.nicl.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic brain networks normalize with treatment in pediatric complex regional pain syndrome

Abstract: Pediatric complex regional pain syndrome (P-CRPS) offers a unique model of chronic neuropathic pain as it either resolves spontaneously or through therapeutic interventions in most patients. Here we evaluated brain changes in well-characterized children and adolescents with P-CRPS by measuring resting state networks before and following a brief (median = 3 weeks) but intensive physical and psychological treatment program, and compared them to matched healthy controls. Differences in intrinsic brain networks we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 119 publications
(152 reference statements)
1
84
1
Order By: Relevance
“…Therefore, other networks may be simultaneously activated during the transmission of pain signals in the brain. Differences in intrinsic brain networks were observed in pediatric complex regional pain syndrome patients as compared to controls, with the most prominent differences in the central executive, default mode, sensorimotor, and salience (anterior insula, mid-cingulate cortex, temperoparietal junction, and dorsolateral prefrontal cortex) networks [161]. Given the extent of neural networks that are affected by chronic pain, it is not surprising that comorbidities (i.e., PTSD, anxiety and depressive disorders) exist among individuals with chronic pain.…”
Section: Potential Neurobiological Mechanisms Underlying Comorbid mentioning
confidence: 99%
“…Therefore, other networks may be simultaneously activated during the transmission of pain signals in the brain. Differences in intrinsic brain networks were observed in pediatric complex regional pain syndrome patients as compared to controls, with the most prominent differences in the central executive, default mode, sensorimotor, and salience (anterior insula, mid-cingulate cortex, temperoparietal junction, and dorsolateral prefrontal cortex) networks [161]. Given the extent of neural networks that are affected by chronic pain, it is not surprising that comorbidities (i.e., PTSD, anxiety and depressive disorders) exist among individuals with chronic pain.…”
Section: Potential Neurobiological Mechanisms Underlying Comorbid mentioning
confidence: 99%
“…Functional imaging studies in paediatric CRPS have shown that in the presence of a nociceptive stimulus (cold and brush), there is increased activity in the affected limb in different basal ganglia regions such as the putamen and globus pallidus and, in contrast to acute pain, decreased activity in the caudate nucleus in comparison to the unaffected side (Lebel et al, 2008;Linnman et al, 2013). Additionally, in the absence of stimuli, children affected by CRPS present altered functional connectivity of the putamen, which normalizes after recovery (Becerra et al, 2014). Additionally, in the absence of stimuli, children affected by CRPS present altered functional connectivity of the putamen, which normalizes after recovery (Becerra et al, 2014).…”
Section: Neuroimaging Findings Linking Crps To Basal Ganglia Dysfunctionmentioning
confidence: 99%
“…The placebo effect is notable in adults and children, and studies that lead to leveraging this impact are needed. Understanding of the common and unique mechanisms of treatments for migraine across the age spectrum is quite limited, and research in this area could have great potential to inform precision-focused care [51-55]. Overall, existing research on migraine treatment suggests that children are not simply ‘little adults’, thus their treatment for migraine should not be handled this way.…”
Section: Discussionmentioning
confidence: 99%